Psychological consequences of perinatal loss: types of distress, risk factors, and adaptation features - Abdriakhimova, Tsira; Kleban, Kateryna (Psychosomatic Medicine and General Practice, 2026)
Background. Each year, more than 2 million stillbirths are recorded worldwide, and perinatal loss occurs in 15–25% of pregnancies. Despite its prevalence, perinatal loss has long remained insufficiently integrated into healthcare systems, and its psychological consequences have not been adequately systematized. Evidence on the comorbidity of psychopathological conditions, risk factors, and adaptive resources remains fragmented and requires further synthesis, particularly in the context of the ongoing war in Ukraine. Objective. To synthesize current evidence on the structure of psychological distress following perinatal loss, as well as risk factors, protective factors, and patterns of adaptation in wartime conditions. Methods. A narrative literature review was conducted using PubMed, Scopus, and Google Scholar databases, with a focus on publications from 2014 to 2025; selected earlier studies were also included due to their conceptual relevance. Original studies, systematic reviews, meta-analyses, clinical guidelines, and classification documents addressing the psychological consequences of perinatal loss were included in the analysis. Results. Perinatal loss is associated with an increased risk of prolonged grief disorder, post-traumatic stress disorder, depression, and anxiety, which frequently co-occur. Risk factors for the development and persistence of psychological distress following perinatal loss include the type and circumstances of the loss, the quality of medical communication, insufficient psychological support, and limited social resources. Protective factors include the effectiveness of coping strategies, relationship quality, social support, and the opportunity for symbolic farewell. In the context of the ongoing war in Ukraine, psychological distress following perinatal loss may be further intensified by chronic stress, forced displacement, and disrupted access to medical and psychological care. Conclusions. The psychological consequences of perinatal loss have a comorbid structure and require a comprehensive clinical approach. The integration of psychological support into perinatal care, as well as the development of trauma-informed models of support, is particularly important in the context of the ongoing war in Ukraine. Keywords: perinatal loss; grief; prolonged grief disorder; post-traumatic stress disorder; depression; anxiety; comorbidity; adaptation; mental health.